Examining how classroom talk shapes students' identities as reflexive writers in elementary classrooms. Issue 1 (2nd January 2022) - Khosronejad, Maryam; Ryan, Mary; Barton, Georgina; Myhill, Debra; Kervin, Lisa
ABSTRACT: This paper works on the premise that classroom talk conveys meaning about students as writers and asks how classroom talk facilitates the formation of students' identities as writers. We present findings from an ethnographic investigation of elementary writing lessons across six participant schools in Australia. Our data analysis is informed by two theoretical constructs that of positioning and implied identity. First, we explore different ways that students are positioned as a result of classroom talk and discuss implied identities – what these positions imply about writer identities within a context. Second, using a micro-ethnographic case study approach, we highlight how participants of classroom talk orient to the acts of positioning within a classroom context. The first section of findings revealed how classroom talk positions students as either autonomous, communicative, metareflexive, or fractured writers. Furthermore, findings showed that the observed writing lessons position students as writers who are concerned with form and pay attention to function. In the second section, we share an in-depth investigation of a year six writing lesson to show how different types of positions are negotiated by teacher and students on a temporal basis. We discuss implications for research and practice related to the teaching of writing.